Comparison of the Shear Bond Strength of Resin Modified Glass Ionomer to Enamel in Bur-Prepared or Lased Teeth (Er:YAG). - Ahmad Jafari; Sima Shahabi; Nasim Chiniforush; Ali Shariat (Tehran University of Medical Sciences, 2013)
The purpose of this study was to evaluate the effect of Er:YAG laser on the shear bond strength of resin modified glass ionomer (RMGI) to enamel.Twenty extracted caries-free human premolars were selected. The teeth were embedded in acrylic resin. The buccal surfaces of each sample were ground to plane enamel with carbonated disc. The teeth were randomly divided in two groups. In the first group, the surfaces were treated by Er:YAG laser (350mJ/10Hz). The second group was prepared by carbide bur. Fuji IX RMGI was adhered to surfaces of the samples in both groups in rod shape. The shear bond strength of samples was measured by a universal testing machine. The results of the two groups were analyzed by T- test.The means and standard deviations of shear bond strength of the laser-treated group and the bur-treated group were 6.75 ± 1.99 and 4.41 ± 1.62 Mpa, respectively. There is significant difference in the shear bond strength of RMGI between the two groups (P-value=0.01).The laser group showed better results. Er:YAG laser can be an alternative technology in restorative dentistry.